The Power Of Concept Mapping To Improve Reading Comprehension - Candra Jaya (Bandar Lampung University (UBL), 2013)
The objective of the study was to investigate the power of concept mapping in improving the students’ reading comprehension at SekolahTinggi Agama Islam Ma’arif (STAI Ma’arif) Metro – Lampung. The study was conducted by using classroom action research within two Cycles. Four steps of each cycle were planning, implementing, observing, and reflecting. Five instruments that are used to collect the data consist of observation sheet, field notes, interview, test, and questionnaire. The findings of the students’ learning atmosphere from observation and fieldnotes described enjoyable of students’ learning interaction. Interview revealed the students felt comfortable and enjoyed for learning reading .The finding of the students’ reading achievement showed that all students, out of 25 students, got the scores above 60. Questionnaire indicated 47% of the students’ responses was “strongly agree” and 53% of their responses was “agree” for the benefit of concept mapping implementation.